ANALISIS PROSES PERENCANAAN PENGANGGARAN HIBAH DAN BANTUAN SOSIAL YANG BERSUMBER DARI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (Studi Pada Dinas Pendapatan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Morowali) - Arifin, Arifin (Katalogis, 2017)
The study aims to determine and describe the process of grant-budgeting and social assistance planning based on the local Revenue and Expenditure Budgets of Morowali Districts. It also means to explore and analyze